Gender-related mental health differences between refugees and non-refugee immigrants - a cross-sectional register-based study - Burström Bo; Bruce Daniel; Hollander Anna-Clara; Ekblad Solvig (BMC, 2011)
Abstract Background Being an immigrant in a high-income country is a risk factor for severe mental ill health. Studies on mental ill health among immigrants have found significant differences in mental health outcome between immigrants from high income countries and low-income countries. Being an asylum seeker or a refugee is also associated with mental ill health. This study aimed to assess if there is a difference in mental ill health problems between male and female refugee and non-refugee immigrants from six low-income countries in Sweden. Methods A cross-sectional, population-based study design was used comparing refugees with non-refugees. The study size was determined by the number of persons in Sweden fulfilling the inclusion criteria at the time of the study during 2006. Outcome: Mental ill health, as measured with the proxy variable psychotropic drugs purchased. Refugee/Non-refugee: Sweden grants asylum to refugees according to the Geneva Convention and those with a well-grounded fear of death penalty, torture or who need protection due to an internal or external armed conflict or an environmental disaster. The non-refugees were all family members of those granted asylum in Sweden. Covariates: Gender and origin. Potential confounders: Age, marital status, education and duration of stay in Sweden. Background variables were analysed using chi square tests. The association between outcome, exposure and possible confounders was analysed using logistic regression analyses. Multiple logistic regression analysis was used to adjust for potential confounders. Results The study population comprised 43,168 refugees and non-refugees, of whom 20,940 (48.5%) were women and 24,403 (56.5%) were refugees. Gender, age, origin, marital status and education were all associated with the outcome. For female, but not male, refugees there was a significantly higher likelihood of purchasing psychotropic drugs than non-refugees (OR = 1.27, 95% CI = 1.15 - 1.40). Conclusions Female refugees from low-income countries seem to be a risk group among immigrant women from low-income countries, whereas male refugees had the same risk patterns as non-refugee immigrants from low-income countries. This underlines the need for training of clinicians in order to focus on pre-migration stress and the asylum process, among female newcomers.